1975
DOI: 10.1007/bf00153288
|View full text |Cite
|
Sign up to set email alerts
|

On the turbulent decay of strong magnetic fields and the development of sunspot areas

Abstract: This paper deals with the conception that two-dimensional turbulence is present in a sunspot where the magnetic field is strong. This conception is based upon the incapacity of even a strong magnetic field to influence an arbitrary two-dimensional turbulence, if the magnetic field is parallel to a constant direction and the motion occurs in planes orthogonal to it. It is, moreover, shown that such a two-dimensional turbulence provides for a turbulent decay of the magnetic field. The decay rate possesses nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Because turbulent diffusion is believed to be the dominating effect of spot decay, the decay rate of spot area is directly proportional to the turbulent diffusivity (Meyer et al 1974;Krause & Rüdiger 1975),…”
Section: Stellar Cycle Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because turbulent diffusion is believed to be the dominating effect of spot decay, the decay rate of spot area is directly proportional to the turbulent diffusivity (Meyer et al 1974;Krause & Rüdiger 1975),…”
Section: Stellar Cycle Predictionmentioning
confidence: 99%
“…Martinez Pillet et al (1993) analyzed sunspot decay rates using the GPR data from 1874-1976 and found a lognormal distribution as well as some evidence for weak nonlinearities in the decay process of isolated spots. A linear area decay law has been studied from a theoretical point of view (Gokhale & Zwaan 1972;Meyer et al 1974;Krause & Rüdiger 1975). Meyer et al (1974) obtained a constant area decrease rate through a process of diffusion of magnetic field over the entire area of the spot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter model, proposed independently by Meyer et al (1974) and by Krause and Rüdiger (1975), assumes that the decay of the spot is caused by turbulent diffusion throughout the whole cross-section of the tube, with a magnetically reduced but otherwise constant diffusivity. It was found that defining the boundary of the spot at some arbitrary fixed value of the flux density, such a diffusion naturally results in a linear decay law, and the Gnevyshev-Waldmeier relation is also returned.…”
Section: Modelsmentioning
confidence: 99%
“…Early theories invoked turbulent diffusion of the magnetic field within the spot to model the observed rate of decay, yet such models predicted a linear decay law, corresponding to a constant area decay rate dA/dt (Meyer et al 1974;Krause & Rüdiger 1975). In order to explain a parabolic decay, Petrovay & Moreno-Insertis (1997) developed a model of sunspot disintegration by turbulent "erosion" of penumbral boundaries, which occurs when bits of magnetic field are sliced away from the edge of a sunspot and swept to the supergranular cell boundaries by supergranular flows (Simon & Leighton 1964).…”
Section: Introductionmentioning
confidence: 99%